Diseño de mobiliario en metal tapizado en cuero para los espacios de ocio en la Facultad de Diseño y Arquitectura de la Universidad Técnica de Ambato - Vasco González, Julian Andre (2025)
This project addresses the design of leather-covered metal furniture for the leisure spaces of the Faculty of Design and Architecture of the Technical University of Ambato, responding to the need for functional and durable elements that encourage social interaction and comfort. The main objective was to design innovative furniture that would optimize the use of spaces, highlighting functionality, resistance and aesthetics. To do so, the Design Thinking methodology was used, allowing an iterative approach that included understanding the needs of users, developing ideas, creating prototypes and evaluating them. Using tools such as Fusion 360, simulations were carried out that guaranteed the stability and safety of the designed furniture. The final result is modular furniture that combines metal and leather, materials selected for their durability and quality, and that adapts to various contexts and needs. This design not only meets the objectives set, but also offers a replicable proposal in other educational environments, highlighting its sustainable approach. It is recommended to explore the incorporation of smart technologies and the use of more sustainable materials in future projects to enhance their impact.